Reassembling management and organisation science: a call for nomadism, transcendental empiricism and creative involution within the field in the face of the grand challenges and the Anthropocene - Gross, Amanda Albuquerque (2023)
This thesis, ambitiously, aims to problematize the common assumptions within Management and Organisation Studies (MOS), as the debates on the Grand Challenges and the Anthropocene, among others, have advocated that our common theoretical and methodological approaches are unable to produce knowledge relevant for dealing with the consequences of those phenomena for the organisational realm. Thus, in this piece, I propose to reassemble the field of MOS by admitting the dependences that we have on other divergent bodies of knowledge, reinforcing the need for new theoretical and methodological approaches, as well as the need to break away from the phallocentrism on which the ‘publicization’ sphere was built. In order to do so, I applied the principles of Deleuzoguattarian philosophy, mainly through the ideas of nomadism, creative involution, cartography, and transcendental empiricism. I also anchor this discussion in key concepts from Actor-network theory, such as translation processes and cartography. Those perspectives are combined with the narrative approach and the feminist perspective of 'dirty' writing, as alternatives to hegemonic ideas of ‘rigour, purity, mastery and masculinity’ within the field. I believe that this proposal could support organisational scholars in reflecting and producing more relevant knowledge for dealing with the consequences of climate change, social inequality and to construct a more diverse social/organisational world. Therefore, the contribution of this thesis is essentially political and philosophical and is supported by some critiques that are already present within the field, and in some discussions around it. In terms of format, this thesis both challenges conventional academic writing norms and emulates the typical structure of a traditional thesis. This was done to engage the readers more with the message, while also serving as a means to test the ideas put forth in the thesis within the field. Finally, it is important to say that the conclusion is more about leaving the questions that guide this thesis open for discussion. The epistemological approaches proposed herein serve as just a few of the many valuable ‘tools’, frameworks and forms of ‘imagery’ for considering our multiplicities, the forces, and the struggles that occur within, and in relation to, the field. Therefore, the main idea is to cultivate reflexivity and awareness in our work in MOS in order to make it more meaningful to the social/organisational realms that are being changed through the transformative emergence of this aberrant new world.